Environmental Accounting Linkage to Sustainable Competitive Advantage and Corporate Social Responsibility - James, Leena (Ushus Journal of Business Management, 2009)
The purpose of this paper is conceptually exploring potential theoretical foundations of environmental accounting based on review and critique of related theories from theoretical foundations of environmental accounting and corporate social responsibilities. It examines the nature of environmental accounting its linkage to sustainability and corporate social responsibilities and describes responding to these aspects.